PENGARUH KEPEMIMPINAN SPIRITUAL TERHADAP KEPUASAN KERJA KARYAWAN MELALUI MOTIVASI INTRINSIK DAN KOMITMEN ORGANISASI (Studi Kasus Rumah Sakit Islam Sultan Agung, Semarang) - Siska Puspitasari (Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine what causes the job satisfaction of a human resource in theorganization. In this test the researcher uses the factors of involvement of a spiritual Leadership,intrinsic Motivation and Organizational Commitment. Tests conducted using SEM AMOS program,the results obtained that spiritual leadership has a significant effect on job satisfaction, intrinsicmotivation also has a significant effect on job satisfaction, and Organizational Commitmentsignificant effect on employee job satisfaction.Keywords: Spiritual Leadership, intrinsic Motivation, Organizational Commitment, JobSatisfaction